The Competency Model of Students' Axiological Culture: Structure, Levels, and Correlations - Pelekh, Yurii (Journal of Education, Health and Sport, 2025)
The research was aimed at a comprehensive assessment of the students’ axiological culture through singling out and experimental testing of five key competences: cognitive, emotional-value, reflective, communicative, and behavioral. For this purpose, a questionnaire was developed; it consisted of 50 statements and used a 4-point Likert scale. The research involved 197 university students from 5 regions of Ukraine. Methods: the statistical analysis included descriptive statistics, nonparametric tests (Mann-Whitney U-test, Kruskal-Wallis H-test), and Spearman rank correlation. Results: the research revealed that the general level of axiological culture of students was sufficient (M = 3.04, SD = 0.47). The highest indicators were recorded for emotional-value (M = 3.16, SD = 0.51) and cognitive (M = 3.09, SD = 0.50) competences. The behavioral competence had the lowest indicators (M = 2.91, SD = 0.52). The research revealed statistically significant differences by gender (U = 3312.5, p = 0.012, r = 0.18) and year of study (H = 15.89, p = 0.007, ε² = 0.07). All competences show strong positive correlations (ρ = 0.72-0.85, p < 0.001). Conclusions: the research results prove that the axiological culture of students is multidimensional in nature, and its development requires a systemic integrative approach. The research emphasized the problem of the gap between value awareness and real behavior, which indicates the need to introduce a significant axiological component into the professional training programs for students.